PERANCANGAN USER INTERFACE APLIKASI MOBILE SEBAGAI MEDIA PROMOSI DIGITAL UMKM INDUSTRI TEKSTIL TAS - AR, Muhammad Bayu Rahmani; Saputra, M. Rizeki Yuda; Shaddiq, Syahrial; Hidayanti, Fahrina; Haikal, Muhammad Fikri (An Nuqud Journal of Islamic Economics, 2025)
Micro, Small, and Medium Enterprises (MSMEs) that produce bags have significant potential for rapid growth in both domestic and international markets. The key lies in leveraging digital promotional media through mobile applications. These apps serve as an effective promotional tool that expands market reach, enhances interaction, and introduces products personally.This research analyzes the potential of mobile applications in the marketing strategies of bag-producing MSMEs, focusing on increasing brand awareness, competitiveness, and sales volume. The results show that mobile applications enable MSMEs to utilize various digital features such like e-commerce, location-based marketing, and push notifications to attract customers. Social media integration also facilitates more effective promotions and strengthens customer loyalty.However, challenges like limited resources and technological understanding among MSME players persist. Overall, utilizing mobile applications for digital promotion offers a great opportunity for MSMEs to expand their market, boost efficiency, and strengthen global competitiveness, provided they are managed strategically and adapt to digital technology